Legislative Vacuum and Its Treatment Mechanism in Iraqi Constitutional Law - Al-Zuhairi, Omar (Journal of Legal Sciences, 2026)
The Iraqi legal system suffers from numerous instances where the application of a legal rule to regulate legal relationships between individuals within both public and private law is absent due to the lack of a text from which the desired legal ruling and regulation of that rule can be derived. sometimes, or it may be impossible to access a ruling despite the existence of a legal text in another country, and for the purpose of adhering to this situation, it is not worthwhile to search for it in light of the basis upon which all legal instructions in the country are based, represented by the specific constitution, and the basis upon which everyone relies in all our laws and legislation.